CCN1 Induces β-Catenin Translocation in Esophageal Squamous Cell Carcinoma through Integrin α11. (31st May 2012) - Chai, Jianyuan; Modak, Cristina; Ouyang, Yi; Wu, Sing-Yung; Jamal, M. Mazen
Abstract : Aims . Nuclear translocation of β-catenin is common in many cancers including esophageal squamous cell carcinoma (ESCC). As a mediator of Wnt signaling pathway, nuclear β-catenin can activate many growth-related genes including CCN1, which in turn can induce β-catenin translocation. CCN1, a matricellular protein, signals through various integrin receptors in a cell-dependent manner to regulate cell adhesion, proliferation, and survival. Its elevation has been reported in ESCC as well as other esophageal abnormalities such as Barrett's esophagus. The aim of this study is to examine the relationship between CCN1 and β-catenin in ESCC. Methods and Results . The expression and correlation between CCN1 and β-catenin in ESCC tissue were examined through immunohistochemistry and further analyzed in both normal esophageal epithelial cells and ESCC cells through microarray, functional blocking and in situ protein ligation. We found that nuclear translocation of β-catenin in ESCC cells required high level of CCN1 as knockdown of CCN1 in ESCC cells reduced β-catenin expression and translocation. Furthermore, we found that integrin α11 was highly expressed in ESCC tumor tissue and functional blocking integrin α11 diminished CCN1-induced β-catenin elevation and translocation. Conclusions . Integrin α11 mediated the effect of CCN1 on β-catenin in esophageal epithelial cells.